Personality and group determinants of forgiveness in the context of inter- and intra-ethnic interactions - Sudnishchikova, Alyona Vladimirovna (Известия Саратовского университета. Новая серия. Серия Акмеология образования: Психология развития)
This study is relevant due to growing inter- and intra-group tensions, which can be alleviated through forgiveness. The aim of the study is to identify how personality and group factors infl uence forgiveness in inter- and intra-ethnic interactions among representatives of diff erent ethnic and language groups. Hypothesis: Personality and group factors – represented by subjective qualities aligned with the mentalities and cultural values of representatives from diff erent ethnic and language groups – signifi cantly infl uence forgiveness in inter- and intra-ethnic interactions. Participants: Students of Korolenkov University (Glazov, Udmurt Republic) aged from 17 to 30 years (N = 249, M = 20.3; SD = 2.8, 88 men, 161 women), grouped into three samples based on their ethnicity and language: Slavic (n = 105), Finno-Ugric (n =7 1), Turkic (n = 73). Methods (tools): The study employed multiple methodologies, including “Methodology for Diagnosing Manifestation of Ethnicity” (V. Yu. Khotinets) to assess objective criteria related to ethnicity, a Russian-language version of the Heartland Forgiveness Scale (adapted by S. K. Nartova-Bochaver, A. A. Adamyan) to diagnose the ability to forgive in inter- and intra-ethnic interaction. Additionally, the research utilized several methodologies to explore personality and group factors, including “Methodology of Self-Attitude Analysis” (S. R. Pantileev), “Short Dark Triad Test” (D. Paulhus, K. Williams, adapted by M. S. Egorov, M. A. Sitnikov, O. V. Parshikov), “PEN” questionnaire (H. Eysenck, S. Eysenck adapted by A. G. Shmelev), “Self-Actualization Test” (E. Shostrom, adapted by L. Ya. Gozman, M. V. Croz), “Tolerance to Uncertainty” (S. Budner, adapted by G. U. Soldatova), “The Diff erential Type of Refl ection” (D. A. Leontiev, E. N. Osin). Results: Acceptance of self-actualizing personality values and systemic refl ection are universal determinants of forgiveness in inter-ethnic interaction. The specifi c determinants of forgiveness of “others” in the Slavic ethnic and language group are agency, activity, integrity; in the Finno-Ugric group – independence of traditional values and behaviors from outside infl uences; in the Turkic group – the level of maturity of personality and systemic refl ection. In the intra-ethnic interaction context, the determinants of forgiveness are proactivity and agency in the Slavic group; in the Finno-Ugric – prosocial orientation; in the Turkic – emotional self-control, prosocial orientation and refl exivity. Main conclusions: Forgiveness that aligns with the mentalities and cultural values of the reference ethnic group manifests proactive behavior of a refl ective personality. Practical Signifi cance: The research results can aid specialists involved in the sociocultural and socio-psychological adaptation of refugees and relocated people.